LEADERSHIP OF THE MADRASAH HEAD IN IMPROVING THE DISCIPLINE OF MADRASAH TEACHERS TSANAWIYAH HAJIJAH AMALIA SARI PADANGSIDIMPUAN - Sukoco, Sugeng (PT Rahis Cendekia Indonesia, 2023)
This research aims to describe the leadership of the madrasa head in improving the discipline of Madrasah Tsanawiyah Hajijah Amalia Sari Padangsidimpuan teachers. The subjects of this research were madrasa heads, teachers and students. This research method is descriptive qualitative using two data collection techniques: interviews and documentation. Data analysis techniques are data reduction, data display, conclusions and data verification. The research results show that the leadership of the madrasa head in improving teacher discipline has been carried out professionally based on the role and function of the madrasa head, so that teacher discipline runs well and the school's vision and mission can be achieved.